(untitled) (Eurasian Journal of Philology Science and Education, 2015)
This article about the different theories of syllable. Syllable is a minimum articulator figure in speech. In the modern linguistics there are a lot of definitions of syllable. Phoneticians have different points of view about theories of syllable expiratory, sonority (acoustic) and muscular tension theory. But for the present there is no definite determination of word- formation, syllable-forming in linguistics.